Biocidal Inactivation of Lactococcus lactis Bacteriophages: Efficacy and Targets of Commonly Used Sanitizers - Hayes, Stephen; Murphy, James; Mahony, Jennifer; Lugli, Gabriele A.; Ventura, Marco; Noben, Jean-Paul; Franz, Charles M. A. P.; Neve, Horst; Nauta, Arjen; Van Sinderen, Douwe (Frontiers in Microbiology, 2017)
Abstract Lactococcus lactis strains, being intensely used in the dairy industry, are particularly vulnerable to members of the so-called 936 group of phages. Sanitization and disinfection using purpose-made biocidal solutions is a critical step in controlling phage contamination in such dairy processing plants. The susceptibility of thirty-six 936 group phages to biocidal treatments was examined using fourteen biocides and commercially available sanitizers. The targets of a number of these biocides were investigated by means of electron microscopic and proteomic analyses. The results from this study highlight significant variations in phage resistance to biocides among 936 phages. Furthermore, rather than possessing resistance to specific biocides or biocide types, biocide-resistant phages tend to possess a broad tolerance to multiple classes of antimicrobial compounds.